Impact of Workload, Occupational Stress, and Remuneration on Staff Turnover Propensity - Shiela Stefani Shiela; Kosasih Kosasih; Ayu Laili Rahmiyati; Vip Paramarta; Farida Yuliaty (Indonesian Journal of Global Health Research, 2026)
This study analyzes the influence of workload, job stress, and compensation on turnover intention among hospital staff in Bandung. Utilizing a quantitative verificative design, data were collected from 103 employees and analyzed via Multiple Linear Regression using SPSS. The research aimed to quantify how these organizational factors collectively and individually drive the propensity of human capital to depart, which is critical in the competitive healthcare sector where replacement costs and knowledge loss are substantial. Descriptive findings reveal that while workload, stress, and compensation levels are currently moderate, the resulting turnover intention remains low. However, inferential analysis confirms a significant impact from all variables. Job stress is the most dominant predictor, uniquely accounting for 31.7% of the variance, followed by compensation (15.8%) and workload (9.2%). Collectively, these three factors explain 56.7% of the total fluctuations in turnover intention ($R^2 = 0.567$). The results demonstrate that workload and stress significantly increase the likelihood of exit, while higher compensation levels effectively mitigate it. These findings suggest that turnover intent is a latent risk highly sensitive to psychological and financial drivers. Management must prioritize proactive retention strategies, specifically targeting stress reduction through clearer job descriptions and improved work environments. Furthermore, maintaining competitive remuneration and equitable workload distribution is essential to prevent moderate dissatisfaction from escalating into actual attrition. By addressing these core determinants, healthcare institutions can stabilize their workforce, preserve institutional knowledge, and ensure the continuity of high-quality patient care.